Meanings attributed by nursing staff about permanent education in cardiovascular institution - Cintia Koerich; Alacoque Lorenzini Erdmann (Rev Rene)
Objective: to understand the meanings attributed by the nursing staff to permanent educational practices in a reference cardiovascular hospital. Methods: this is a qualitative study, which used the Grounded Theory in Data for collecting and analyzing data. The sample consisted of 22 nursing professionals. Results: the study presents two categories that highlight the need for further clarification of the nursing staff about the concept of permanent education in health, as well as reinforce the permanent education of nurses as a management practice which needs to be incorporated into other assignments in daily work. Conclusion: it is admitted the need to work the concepts of permanent education in health even in professional qualification, as well as place greater emphasis on managerial training of nurses, so they acquire the power to take their assignment as a nursing care manager and the nursing staff education contribute to the necessary changes in the health services.